2008
DOI: 10.1021/jp7099702
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Water Gas Shift Reaction on Pt:  First Principles, Experiments, and Microkinetic Modeling

Abstract: We present a microkinetic model as well as experimental data for the low-temperature water gas shift (WGS) reaction catalyzed by Pt at temperatures from 523 to 573 K and for various gas compositions at a pressure of 1 atm. Thermodynamic and kinetic parameters for the model are derived from periodic, self-consistent density functional theory (DFT-GGA) calculations on Pt(111). The destabilizing effect of high CO surface coverage on the binding energies of surface species is quantified through DFT calculations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

86
605
8
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 470 publications
(706 citation statements)
references
References 48 publications
(85 reference statements)
86
605
8
3
Order By: Relevance
“…20 In summary, we corrected the enthalpy of O 2 adsorption using our more accurate reflectivity of 76% and show that it gives nearly identical results below 0.15 ML to the heats of adsorption determined from TPD experiments. 2,3 We further use these corrected adsorption enthalpies to amend the energetics of hydroxyl species on Pt (111) Fig.…”
Section: Enthalpies For Reactions Involving Surface Hydroxyls On Pt(111)mentioning
confidence: 73%
“…20 In summary, we corrected the enthalpy of O 2 adsorption using our more accurate reflectivity of 76% and show that it gives nearly identical results below 0.15 ML to the heats of adsorption determined from TPD experiments. 2,3 We further use these corrected adsorption enthalpies to amend the energetics of hydroxyl species on Pt (111) Fig.…”
Section: Enthalpies For Reactions Involving Surface Hydroxyls On Pt(111)mentioning
confidence: 73%
“…~0.6 eV lower than direct dissociation. In principle, direct hydrogenation of CO 2 to formate (HCOO) could also occur but this involves a much higher energy barrier ( 58 or kinetic Monte Carlo 59 algorithms. Nevertheless, it is worth pointing out that kinetic experimental data and the theoretical energy barriers show similar trends.…”
Section: Computational Studymentioning
confidence: 99%
“…3,4 They found that formate, an intermediate involved in formic acid production, is a spectator species for the WGS reaction. The energy barriers for adding an adsorbed H atom to physisorbed CO 2 to form formate are 1.02 and 1.39 eV on Cu(111) and Pt(111), respectively.…”
Section: Introductionmentioning
confidence: 99%